Characterization of debonding in FRP-strengthened masonry using the acoustic emission technique - Ghiassi, Bahman (2014)
The acoustic emission (AE) technique is used for investigating the interfacial fracture and damage propagation in GFRP- and SRG-strengthened bricks during debonding tests. The bond behavior is investigated through single-lap shear bond tests and the fracture progress during the tests is recorded by means of AE sensors. The effect of hygrothermal conditions on the debonding characteristics and failure mode is also investigated by performing accelerated ageing tests. Accelerated ageing tests resulted in a change of failure mode in GFRP-strengthened specimens which helped in assessment of AE output in different failure modes, but no conclusive strength degradation was observed in the specimens. The results show that the average and cumulative AE energy are correlated to the FRP slip and debonding fracture energy in GFRPstrengthened specimens, respectively. The fracture progress and active debonding mechanisms are characterized using results from the AE technique. Moreover, a clear distinction between the AE outputs of specimens with different failure modes, in both SRG- and GFRP-strengthened specimens, is found which allows characterizing the debonding failure mode based on acoustic emission data. The tests performed in this study are also a contribution towards the application of AE techniques for on-site health monitoring of strengthened masonry structures.